Media access control for Ethernet passive optical networks an overview. - Zheng, Jun (IEEE Communications magazine)
Medium access control is one of the crucial issues in the design of Ethernet passive optical networks. To ensure efficient transmission, an EPON system must employ a MAC mechanism to arbitrate access to the shared medium in order to avoid data collisions in the upstream direction and at the same time efficiently share the upstream transmission bandwidth among all ONUs. The purpose of this article is to provide a good understanding of the MAC issue, discuss the major problems involved (e.g., multiple access, bandwidth allocation, transmission scheduling, and quality of service support), and present an overview of the state-of-the-art solutions proposed thus far to the problems. It is also our purpose to motivate further studies on the problems described in this article.